2019
DOI: 10.5204/ijcjsd.v8i2.1010
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Realities of Violence in Medellín, Colombia

Abstract: Latin America is one of the most violent regions in the world, and this is particularly evident in its many cities. While urban violence scholars and policymakers generally rely on homicide rates to measure levels of violence in urban environments, these objective indicators often do not capture its realities. By drawing from over six months of fieldwork in the Latin American city of Medellín, Colombia, this paper shows how Medellín has experienced a significant reduction in homicides, but both real and percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Further, the local media may even sensationalise actual levels of violence. Previous research has www.crimejusticejournal.com IJCJ&SD 89 2020 9(3) shown that in Latin America, there are discrepancies between perceived levels of crime and reported levels of crime (Corbacho, Philipp and Ruiz-Vega 2012;Doyle 2019b;Restrepo and Moreno 2007;Sanguinetti et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the local media may even sensationalise actual levels of violence. Previous research has www.crimejusticejournal.com IJCJ&SD 89 2020 9(3) shown that in Latin America, there are discrepancies between perceived levels of crime and reported levels of crime (Corbacho, Philipp and Ruiz-Vega 2012;Doyle 2019b;Restrepo and Moreno 2007;Sanguinetti et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, by 2018 this figure reduced to 27 per 100,000, translating to a 95% reduction in homicides. Researchers have acknowledged how despite this decline, different forms of violence continue to have an impact on the lives of residents (Abello-Colak and Pearce 2015;Abello-Colak and Guarneros-Meza 2014;Dávila 2018;Doyle 2019aDoyle , 2019b. Further, and similar to other Latin American cities, Medellín continues to experience high levels of distrust in public institutions and residents generally do not feel safe, despite reductions in reported levels of crime (Medellín Como Vamos 2015;Sanguinetti et al 2014).…”
Section: Medellín Colombiamentioning
confidence: 99%
See 1 more Smart Citation
“…The so‐called ‘Medellín Model’ (Bahl, 2012; Brand and Davila, 2011; Maclean, 2015) was taken up in varied guises in other cities, such as Monterrey and Ciudad Juarez in Mexico and Rio de Janeiro in Brazil (Gay, 2017), where new ‘models’ emerged. The limitations of the security model in Medellín have become apparent (Doyle, 2019; Humphrey and Valverde, 2017). Local gangs and criminal organizations in Medellín, as in other cities such as Sao Paulo and Rio de Janeiro, still have strong influence in marginalized communities despite increased state intervention, not only because they exercise violent forms of social ordering and conflict management, but because they have inserted themselves in the provision of local services (Abello Colak and Guarneros‐Meza, 2014; Blattman et al., 2021; Davila, 2018; Feltran, 2020).…”
Section: The Objective and Subjective Crisis Of Security In Latin Americamentioning
confidence: 99%